Democratização do acesso a água no semi-árido: o caso da comunidade rural de Pendências dos Emídios no município de Serrinha/RN - Pimentel, Remo Rene (2008)
Brazil lives a time of experimentation and maturity as it pertains to managing the use of water, which comes institutionalising increasingly social participation. In Rio Grande do Norte, since 1997, the government has been developing actions accordingly, through the State Department of Water Resources, which has implemented a programme of adutoras within the State and created Water Users Associations, in the installation of dessalinizadores for places where the Adutora was not necessary or not yet arrived, so that should be managed by communities through associations of users. Since 2003, Civil Society Organisations - CSOs come through ASA - Articulation in the Semi-arid Brazilian, implementing the P1MC - Program of Training and Mobilization for Social Living with the Semi-Arid (One Million Rural Cisternas), in its third year of implementation in Rio Grande do Norte, in the spirit of working together with the semi arid. In the municipality of Serrinha / RN which incorporates the Semi-arid region, we find in the rural community of Pendêcias dos Emídios the experience of the State and Civil Society, which referred to a discussion about the environmental sustainability of these initiatives. The general objective of this work is to examine the strategies for participatory management in the use and access to water in the community of Pendêcias dos Emídios of the municipality of Serrinha / RN, to understand how those experiences can contribute to environmental sustainability. The methodology used envolvel bibliographic research in categories involving each article, the analysis of the terms of reference of each strategy as part of the documentary research, the application forms covering 40 families benefited, and interviews based on comprehensive analysis of the speech. This study is divided into 02 articles, where the first is a discussion held on collective action and environmental sustainability, and the second is held a discussion about the sustainability of the initiatives underway to access water. The results of the discussion held on 02 articles that had their empirical built from the experience of the Commonwealth of Pendências dos Emídios revealed how far will the ability of the State to promote collective action and the limitations of the perception of sustainability that permeates these initiatives in the search for democratic access to water in semi-arid